Kendala Guru dalam Pengembangan Materi IPS Terpadu dan Upaya Mengatasinya di MTS Islamiyah Medan - Widya Khairunisa; Clarissa Oktoferin Sinaga; Elsy Nila Sari Situmeang; Esra Silaban; Fadilla Khoiri; Mita Nalsalisa Br Barus; Shika Andari; Angelo Arevallo Simanullang (Pusat Riset dan Inovasi Nasional, 2025)
Integrated Social Studies (IPS) is a highly potential learning approach to improve the quality of IPS learning. However, the development of integrated IPS materials still faces various challenges. The purpose of this research is to focus on the main problem, namely, there are several challenges faced by teachers in developing integrated IPS materials. Therefore, efforts are made to overcome these problems in MTS Islamiyah Medan. The method used in this research is through interviews, observations, and documentation. The results obtained include the constraints of limited learning resources, the challenges of integrating IPS materials, educational background, and the lack of facilities such as technology.